A Female Pseudohermaphroditism with Pyometra in a Dog: A Case Report - Swasdipan, Chayut; Sutthikan, Somchin; Suraruji, Nattachai (Journal of Mahanakorn Veterinary Medicine, 2020)
A five-years-old intact male Siberian husky dog was presented to the hospital with abdominal enlargement and abdominal cramp. Physical examination showed abdominal enlargement, external genitalia like a female characteristic and testes were absence. Rectal palpation found a massive mass at ventral to the colon. Blood results revealed leukocytosis and thrombocytopenia. Abdominal radiograph revealed a mass located between urinary bladder and colon. Abdominal ultrasound revealed a tubular-like structure with irregular and thickening wall and contains with echogenic fluid. Both ovaries presented at caudal to kidneys. The female pseudohermaphroditism and pyometra was diagnosed. Surgical correction by ovariohysterectomy. Medical treatment with antibiotics and analgesia drugs was performed for 14 days. Fourteen days after surgery, the dog presented normal in clinical signs and blood results.